The Narrative-Theological Function of Matthew’s Baptism Command (Matthew 28:19b) - S. THELLMAN, Gregory (Anafora, 2023)
The triadic name given in the baptism command of Matthew 28:19b has often been considered awkward in its context and perhaps anachronistic in light of later Christian Trinitarian doctrine. This article argues that Matthew 28:19b is rather a fitting climactic conclusion to a narrative-theological motif throughout Matthew’s Gospel where triadic or at least dyadic language is employed within revelatory contexts that affirm Jesus’ divine sonship and messianic mission: either in small apocalypses or within apocalyptic discourse. This argument finds its crux in the baptism of Jesus itself (3:13–17) which is presented as an apocalypse in which the heavenly fatherly voice reveals the identity of the Son and anoints him with his Spirit, with the stated goal of “fulfilling all righteousness.” The revelation is presented by Matthew so that it is directed to the public within the narrative and implicitly to the reader disciple. The baptism revelation is then closely associated both with the lengthy citation of Isaiah 42:1–4 in Matthew 12:18–21, another triadic text, and with the visionary transfiguration account (17:1–8). Other passages are analyzed in order to trace the pattern throughout the Gospel. In the resurrection narrative (28:1–20) it is demonstrated that the resurrected Jesus is portrayed as a now heavenly, yet still embodied, revealer who is worshipped such that the Great Commission passage (28:16–20) is presented as a divine revelation. Within this “ultimate apocalypse” the risen Jesus commands his followers to make disciples of the nations by teaching and baptizing in the triadic name. The baptism command, in light of the triadic motif throughout the Gospel has the rhetorical effect of inviting Matthew’s reader-listener disciples to identify with Jesus in his own triadic baptism such that they too have an affirmed filial relationship with God and receive the anointing of the Holy Spirit to continue and extend Jesus’ messianic mission into the world under his universal authority and with his promised presence.